The Urgency of Limiting the Use of the Veto in the UN on Security Resolutions and Global Political Stability - Ramadhani, Setiawan; Sihabuddin, Ahmad; Chalissa, An Naja Putri; Mustiana, Sasti Rizky; Rosida, Zakia (Faculty of Law, Universitas Jenderal Soedirman, 2024)
This article examines the implications of the veto power held by the five permanent members of the United Nations Security Council (UNSC) on international conflict resolution and global political stability. The research employs a normative legal methodology, analyzing the UN Charter and relevant historical documents to understand the evolution and application of veto rights. The primary objectives are to assess how the veto affects the UNSC's effectiveness in responding to crises, as illustrated by the Syrian civil war and Russia's invasion of Ukraine, and to explore potential reforms aimed at democratizing decision-making processes within the UN. The findings reveal that the frequent use of vetoes creates significant deadlock, undermining multilateral efforts to address urgent humanitarian issues and exacerbating global instability. Furthermore, the study discusses various reform proposals, such as limiting veto usage in cases of mass atrocities and enhancing participation from non-permanent members. In conclusion, while the veto power was originally intended to ensure cooperation among major powers, its current application often leads to paralysis within the UNSC, necessitating urgent reforms to restore legitimacy and effectiveness in maintaining international peace and security. This research contributes to ongoing debates about reforming global governance structures to better reflect contemporary geopolitical realities and promote collective security over national interests.Keywords: Veto; United Nations; Securtiy Resolutions; Global Political Stability; Global Politic Dynamics.